The Role of Credit Default Swaps on Financial Market Stability - TERZİ, NURAY (ELSEVIER SCIENCE BV, 2011)
The role of credit default swaps (CDS) in the financial crisis has been debated among regulators, market participants and academics since early 2008. CDSs are derivative instruments which enable market participants to transfer or redistribute credit risk. However, the size of the CDS market, combined with its structural opacity, concentration and interconnectedness, may be a sign that the CDS market also poses a systemic risk to financial market stability. The purpose of the article is to investigate the role of credit default swaps on financial market stability. The impact of credit default swap markets on financial market stability crucially depends on market mechanisms, and capital-liquidity requirements in financial markets. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Credit default swaps; financial market stability; systemic risk; counterparty risk